2021
DOI: 10.3390/antiox10111853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Melatonin Supplementation on Visual Loss, Circadian Rhythms, and Hepatic Oxidative Damage in a Rodent Model of Retinitis Pigmentosa

Abstract: Retinitis pigmentosa (RP) is a group of inherited neurodegenerative diseases characterized by a progressive loss of visual function that primarily affect photoreceptors, resulting in the complete disorganization and remodeling of the retina. Progression of the disease is enhanced by increased oxidative stress in the retina, aqueous humor, plasma, and liver of RP animal models and patients. Melatonin has beneficial effects against age-related macular degeneration, glaucoma, and diabetic retinopathy, in which ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In this case, their circadian rhythms would be expected to exhibit a non-24-hr pattern. A recent study has shown that melatonin supplementation decreased the rate of desynchronization of the circadian rhythm and improved visual function in P23H rats [90]. This provides a new possibility for treating RP through circadian synchronization and hence it is important to understand the changes in the circadian pattern in different models of RP to get a better understanding of the role of circadian rhythm on RP.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, their circadian rhythms would be expected to exhibit a non-24-hr pattern. A recent study has shown that melatonin supplementation decreased the rate of desynchronization of the circadian rhythm and improved visual function in P23H rats [90]. This provides a new possibility for treating RP through circadian synchronization and hence it is important to understand the changes in the circadian pattern in different models of RP to get a better understanding of the role of circadian rhythm on RP.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin supplementation (in drinking water) in P23HxLE rats, a model that resembles the clinical features of heterozygous patients with RP, improved visual acuity, contrast sensitivity and retinal electrical activity [ 168 ]. It also improved circadian synchronization and increased the levels of CAT and SOD, which further reduced oxidative stress.…”
Section: Therapeutic Strategies To Reduce Oxidative Stress and Inflam...mentioning
confidence: 99%
“…One of these antioxidants is melatonin [5]. Melatonin, which is N-acetyl-5-methoxytryptamine, can be synthesized from tryptophan (an essential amino acid) and produced from (the brain) pineal gland, (eye) retina and lacrimal gland, digestive system, and other organs [6]. Melatonin has very important functions in regulating the circadian rhythm, cardiovascular function, regulating the immune system, vague retinal functions, and pancreatic function.…”
Section: Introductionmentioning
confidence: 99%